Análise numérica de fissuramento em barragens de terra através da técnica de variação de rigidez - Maia, Romário Anderson Guerreiro (2022)
The improvement of knowledge about unsaturated soils has evolved in order to improve the modeling of earthworks projects, since the unsaturated condition is present throughout the useful life of a wide variety of geotechnical works. Small earth dams have been used since ancient times and are often the main source of water. In this particular type of work, studies on soils reveal that under water saturation, changes occur in their mechanical properties, generally causing a simultaneous loss of stiffness and shear strength. Thus, during the first filling of a reservoir, the earth masses can suffer deformations caused by changes in the state of stress in the landfill, which can cause the appearance of cracks. In this context, the UNSTRUCT program appears, which is a program directed to calculate the final state of stress/strain for a plane strain state, using the Finite Element Method in saturated and unsaturated masses, using an elastic model and considering the effect of suction and its variation, through the technique of variation of stiffness. In the present research, a hypothetical study was carried out, using the UNSTRUCT, of the body of a dam, varying the following characteristics of a cross-section type: homogeneity; internal filtering structures; geometry along a longitudinal profile; influence of the level of compaction and zoning between cores and backrests. The UNSTRUCT program proved to be efficient in obtaining and visualizing the results, also making it possible to analyze the development of the collapse over time, considering any time intervals after the simulated dam was filled. As results obtained, it can be mentioned that the soil responds better to deformations for the condition of better compaction along the dry branch of the compaction curve, as well as with the use of a filtering element. It was observed that the deformations are greater the greater the sections considered, which can cause distortions along the longitudinal profile of a dam. It was also observed that the compaction of a specific zoned part (core or backrests) can lead to the occurrence of traction zones, being possible points of crack formation.